Physical and Mechanical Behaviour of Silane-Modified Coconut Inflorecence/Glass Fibril-Fortified Hybrid Epoxy Composites - R. Jayachitra; M. S. Srinivasa Rao; Anil Kumar Bodukuri; Eyuel Abate Lemma (Advances in Materials Science and Engineering)
Augmenting concern towards effective utilization of agro waste into useful products has fomented the scientific community to look for alternate source of materials. On circular economy contemplation, natural fibers extricated from agro waste have a potential headway towards evolution of newer materials. Natural fiber hybridized with glass fiber and fortified with epoxy matrix has been found to be a promising material with unique characteristics to suit a wide variety of applications. The hydrophilic natural fibers have a resistance to bind with the polymer matrix; as a result, interfacial adhesion is limited, thereby mechanical properties of the composites are not much appreciable. In this present research, the lignocellulose fibrils extracted from coconut inflorescence were subjected to three types of silane modifications, namely, KH550 (amino silane), KH560 (epoxy silane), and KH570 (methyl silane) before hybridization. The effect of silane modification on the functional groups was investigated. The KH570 silane-modified inflorescence fiber hybridized with glass fiber and fortified epoxy composites were found to exhibit utmost tensile and flexural strengths of 102.6 MPa and 166.89 MPa, respectively. FTIR analysis confirmed KH570 silane modification leads to condensation reaction between interface of fibers and matrix. SEM analysis also confronted the elimination of functional groups present in the coconut inflorescence fibers.